อิทธิพลของปัจจัยจูงใจต่อพฤติกรรมการซื้อเสื้อผ้าแฟชั่นผ่านเว็บไซต์อิเล็กทรอนิกส์คอมเมิร์ซ - พิชชาพร เนียมศิริ (จุฬาลงกรณ์มหาวิทยาลัย, 2017)
This quantitative survey was intended to investigate the influences of factors of buying fashion apparel on electronic commerce websites (which consisted of website quality, apparel product attributes and consumer characteristics) on (1) consumer attitude and (2) purchase intention. Self-administered questionnaires were used to collect data form 400 males and females, aged 18-35 years old in Bangkok, who had bought fashion clothes from electronic commerce websites in the last three months. The findings showed that fashion product attributes and consumer characteristics significantly and positively influenced consumer attitude and purchase intention in buying fashion apparel on electronic commerce websites for both marketplace and brand websites.